Incremental increases in economic burden parallels cardiometabolic risk factors in the US - McQueen RB; Ghushchyan V; Olufade T; Sheehan JJ; Nair KV; Saseen JJ (Diabetes, Metabolic Syndrome and Obesity, 2016)
R Brett McQueen,1 Vahram Ghushchyan,1,2 Temitope Olufade,3 John J Sheehan,4 Kavita V Nair,1 Joseph J Saseen1,5 1Department of Clinical Pharmacy, University of Colorado Skaggs School of Pharmacy and Pharmaceutical Sciences, Anschutz Medical Campus, Aurora, CO, USA; 2College of Business and Economics, American University of Armenia, Yerevan, Armenia; 3AstraZeneca, Wilmington, DE, 4AstraZeneca, Fort Washington, PA, 5Department of Family Medicine, University of Colorado Anschutz Medical Campus, Aurora, CO, USA Objective: Estimate the economic burden associated with incremental increases in the number of cardiometabolic risk factors (CMRFs) in the US. Methods: We used the nationally representative Medical Expenditure Panel Survey from 2010 to 2012 to create a retrospective cohort of people based on the number of CMRFs (one, two, and three or four), and a comparison cohort of people with zero CMRFs. CMRFs included abdominal obesity, elevated blood pressure, elevated triglycerides, and elevated glucose and were defined using diagnostic codes, prescribed medications, and survey responses. Adjusted regression analysis was developed to compare health expenditures, utilization, and lost-productivity differences between the cohorts. Generalized linear regression was used for health care expenditures, and negative binomial regression was used for utilization and productivity, controlling for individual characteristics. Results: The number of CMRFs was associated with significantly more annual utilization, health care expenditures, and reduced productivity. As compared with people with zero CMRFs, people with one, two, and three or four CMRFs had 1.15 (95% confidence interval [CI]: 1.06, 1.24), 1.37 (95% CI: 1.25, 1.51), and 1.39 (95% CI: 1.22, 1.57) times higher expected rate of emergency room visits, respectively. Compared with people with zero CMRFs, people with one, two, and three or four CMRFs had increased incremental health care expenditures of US$417 (95% CI: $70, $763), US$2,326 (95% CI: $1,864, $2,788), and US$4,117 (95% CI: $3,428, $4,807), respectively. Those with three or four CMRFs reported employment of 60%, compared with 80% in patients with zero CMRFs. People with three or four CMFRs had 1.75 (95% CI: 1.42, 2.17) times higher expected rate of days missed at work due to illness, compared with people with zero CMRFs. Conclusion: Our findings demonstrate a direct association between economic burden and number of CMRFs. Although this was expected, the increase in burden that was independent from the cost of cardiovascular disease was surprising. Keywords: economic burden, cardiometabolic risk factors, cardiovascular disease